The Role of Philosophy of Science in Strengthening Human Resource Management Research and Practice - Syafira Ramona, Nur; Hidayat , Sarah Nursa’diah; Veranita, Mira (International Journal Administration, Business & Organization, 2026)
Human Resource Management (HRM) has developed into a strategic and knowledge-based discipline, yet many studies apply theoretical and analytical approaches without explicitly examining the philosophical assumptions underlying HRM research and practice. This limited reflection may reduce theoretical coherence, methodological consistency, and ethical accountability. This study examines how the ontological, epistemological, and axiological dimensions of the philosophy of science contribute to strengthening the theoretical, methodological, and ethical foundations of Human Resource Management. Using a qualitative thematic literature review, 54 academic publications published between 2018 and 2025 were systematically analyzed through iterative coding and thematic synthesis. The findings show that philosophical assumptions are widely embedded but rarely made explicit in HRM research. Ontological perspectives are often rhetorical, epistemological approaches are dominated by quantitative and data-driven methods, and axiological considerations are acknowledged but weakly institutionalized. This uneven integration sustains a gap between philosophical principles and HRM practice. The study proposes an integrative conceptual model linking philosophical dimensions to HR practices and organizational outcomes. The study concludes that philosophy of science can serve as a reflective framework to support more coherent, ethically grounded, and context-sensitive HRM research and practice.